Delay-Dependent Stability of Networked Generator-Excitation Control Systems: An LMI based Approach∗. Issue 1 (2016) - Ramakrishnan, K.
Abstract: In this paper, using Lyapunov-Krasovskii functional approach combined with Wirtinger inequality, a less conservative stability criterion (sufficient condition) in linear matrix inequality (LMI) framework is presented for ascertaining the delay-dependent stability of a network controlled generator-excitation control system. A PI controller based generator-excitor control system (Automatic Voltage Regulator (AVR)) with time-invariant feedback loop delays is considered for the stability analysis. The delay-dependent stability problem is formulated by mathematically modeling of the closed-loop system as a linear retarded continuous-time delay-differential equation with incremental system variables as state variables. Subsequently, by using the LMI based stability criterion, maximum allowable bound of the network delay that the closed-loop system can accommodate without losing stability is computed for various subset of the controller parameters. The effectiveness of the proposed result is validated on a bench-mark AVR system with simulation results.